Characterizing fretting damage in different test media for cardiovascular device durability testing. (June 2018) - Weaver, J.D.; Ramirez, L.; Sivan, S.; Di Prima, M.
Abstract: In vitro durability tests of cardiovascular devices are often used to evaluate the potential for fretting damage during clinical use. Evaluation of fretting damage is important because severe fretting can concentrate stress and lead to the loss of structural integrity. Most international standards call for the use of phosphate buffered saline (PBS) for such tests although there has been little evidence to date that the use of PBS is appropriate in terms of predicting the amount of fretting damage that would occur in vivo . In order to determine an appropriate test media for in vitro durability tests where fretting damage is being evaluated, we utilized an in vitro test that is relevant to cardiovascular devices both in terms of dimensions and materials (nitinol, cobalt-chromium, and stainless steel) to characterize fretting damage in PBS, deionized water (DIW), and heparinized porcine blood. Overall, tests conducted in blood were found to have increased levels of fretting damage over tests in DIW or PBS, although the magnitude of this difference was smaller than the variability for each test media. Tests conducted in DIW and PBS led to mostly similar amounts of fretting damage with the exception of one material combination where DIW had greatly reduced damage compared to PBS and blood. Differences in fretting damage among materials were also observed with nitinol having less fretting damage than stainless steel or cobalt-chromium. In general, evaluating fretting damage in PBS or DIW may be appropriate although caution should be used when selecting test media and interpreting results given some of the differences observed across different materials. Graphical abstract: fx1 Highlights: Overall, fretting damage was greater in blood than PBS or DIW but not in all cases. Nitinol experienced less fretting damage than stainless steel or cobalt-chromium. Fretting damage was equivalent in PBS and DIW for most but not all cases.